La disgrafía y su influencia en el rendimiento académico de los estudiantes de 4to año de educación general básica de la unidad educativa réplica Simón Bolívar - Veloz García, Delia María (2019)
The present research aims, addressing Dysgraphia as one of the educational problems in the 4th year of education General basic of the unit educational Replica Simón Bolívar in Guayaquil city teaching period 2017-2018, which is they detect problems of writing as: the outline of the letters, the inclination of the letters on the lines, the disproportionate graphemes, combination of letters with lowercase causing a real inconsistency in writing. The methodology applied in this project allowed to gather direct information. Is based on the quantitative approach, in the documentary field research, descriptive and explanatory, the theoretical framework properly supported, with the use of the questionnaire technique applied diagnostic assessment tests the in that it has allowed to detect the degree of difficulty of the writing of students, in addition direct observation method, whereby it was verified the educational needs, and the specific difficulties of writing that each student presents by the who proceeded to develop methodological intervention strategies to improve writing in children, constituted by eight pieces which encompass skills, activities, resources and evaluation indicators accompanied by documents of monitoring to be applied by teacher, thus allowing overcome academic performanc……..